Development of the Programme of Applied Research as a Tool for the Formation of Research Competency of Future Political Scientists (on the Example of the Theme "Spatial Development of Russia as a Factor in Nation-Building and National Idea Formation") - O. V. Bakhlova; I. V. Bakhlov; I. G. Napalkova; A. S. Soldatova (Russian State Vocational Pedagogical University, 2019)
Introduction. Nowadays, the modern higher education involves not only advanced theoretical training, but also the formation of practical skills and universal professional skills, which contribute to the development of skills of future specialists and their successful careers. The participation of students in the research work is considered as a special direction of improvement of professional competency and an essential factor of general cultural development of the student's personality. The research work creates prerequisites for qualitative change of the whole working practice through the acquisition of abilities to act reasonably in working situations, to solve tasks and problems independently and effectively, to assess the results of own work adequately. However, the active inclusion of students in research activities was characterised by the lack of guidelines, which could be used to fill the gaps in research methodology and research procedures. This fully applies to the students of political science specialties and updates the interpretation of research and political science practices.The aim of the article is to reveal the peculiarities of organisational and technological procedures of complex socio-political applied research, using a specific example of a training model.Methodology and research methods. The authors used general scientific and special methods and approaches: formalisation, abstraction, comparative analysis, system-based and conceptual approaches, etc. An interview was conducted as the main applied method to diagnose the degree of students' (bachelor's and master's degree students training in the discipline "Political Science" at Ogarev Mordovia State University) interest in research work and their understanding of the importance of practice-oriented learning.Results and scientific novelty. On the basis of the studentsэ questionnaire responses, the factors characterising the problem situation "Quality of Student Research Work", are worked out in detail. The survey questionnaire revealed that the research work is perceived by students as a qualification component for obtaining master's / bachelor's degrees, but not as an important element of professional development. A good level of theoretical knowledge of the subject area is frequently negated by the low development of practical skills, including due to the unwillingness or lack of opportunity to participate in practice-oriented research. However, the majority of respondents (77.7%) stated that they lack available information sources on the methodology of specific scientific papers with examples in order to indeppendently choose the research strategy and to develop their own professional skills. In this regard, on the example of the topic "Spatial Development of Russia as a Factor of Nation-Building and Formation of National Idea", a universal programme of political applied research was developed. The programme can be used as a basis for long-term analysis and as a template for other thematic studies. The proposed scheme includes the selection of analysis methods and techniques to maximise the scope of the study area.Practical significance. The described research methodology can be used in educational practice, when teaching the following disciplines: "Methods and Technologies of Political Science", "Information and Analytical Work", "Political Analysis and Forecasting", etc.